Analysing the Management of Waste and Leachate in the Final Disposal Site of Indramayu - Indah Dhamayanthie; Erbi Bimantara; Ninin Asminah (Indonesian Journal of Multidisciplinary Science, 2021)
Garbage is waste material from household, commercial, industrial or other human activities. Waste generation is the volume of waste or the weight of waste generated from types of waste sources in a certain area per unit of time. The final destination of the waste is to be processed at the Final Processing Site (TPA). In Indramayu, the waste generation is quite large and can cause environmental pollution, so there is a need for good waste management. The purpose of this study is to determine the waste management system in TPA Indramayu, to determine the amount and average of waste, to determine the generation and volume of waste and to determine the levels of BOD, COD and effectiveness in the leachate treatment unit. From the results of observations, it was found that the average receipt of waste at TPA Indramayu was 177,451 tons/day. The waste generation is known to be 2.75 l/or/day and the resulting volume of waste that goes to the TPA is 777,284 m3/hr and the volume of waste per region is 0.003 m3/or/day. The incoming leachate comes from the landfill area and is then processed in the WWTP unit with 4 holding ponds to reduce BOD and COD levels. The initial BOD level entered was 500 mg/L and the incoming COD level was 4000 mg/L, after going through the leachate treatment the results obtained were BOD levels of 33.34 mg/L and COD levels of 266.66 mg/L with efficiency BOD and COD conversion of 93.33%.